High-strength ivory white ceramic glaze, ceramic having the glaze and preparation method thereof
By using high-strength ivory white ceramic glaze in ceramic products, combined with raw materials such as Dehua quartz, Dehua kaolin, Dehua potassium feldspar and doped modified fillers, the problems of insufficient compressive strength, fracture toughness and acid-base corrosion stability of ceramic products are solved, and the uniformity of ivory white color and high-performance ceramic products are achieved.
Patent Information
- Application Number
- CN202411894904.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-21
AI Technical Summary
Existing ceramic products have shortcomings in compressive strength, fracture toughness and acid-base corrosion stability, and are difficult to coordinate evenly with the ivory white color.
High-strength ivory white ceramic glaze, including Dehua quartz, Dehua kaolin, Dehua potassium feldspar, doped modified filler balance agent, chitosan liquid and calcium stearate, are used to improve the coordination and sintering of raw materials through ball milling and sintering.
The high compressive strength, fracture toughness and ivory white color of ceramic products are achieved, and the stability is significantly improved under acid-base corrosion conditions.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramics, and in particular to a high-strength ivory white ceramic glaze, a ceramic having the glaze and a preparation method thereof. Background Art
[0002] Ceramics is a general term for pottery and porcelain. Common ceramic materials include clay, alumina, kaolin, etc. Ceramic materials are generally hard but have poor plasticity. In addition to being used in tableware and decoration, ceramics also play an important role in the development of science and technology. Ceramic raw materials are made by quenching clay, a large amount of original resources on the earth.
[0003] Ivory white porcelain is one of the most distinctive and well-known varieties of Dehua white porcelain. It is a treasure that was used in large quantities in the Ming Dynasty. The porcelain is tough, thick, delicate and warm. The porcelain color is white with yellow, just like ivory, hence the name ivory white.
[0004] In order to make the existing ceramic products ivory white, Dehua feldspar and other raw materials are added. However, the compressive strength and fracture toughness of the ceramics are difficult to coordinate with the ivory white and uniform color of the product. At the same time, the product has poor stability under acid and alkali corrosion conditions, which limits the product's efficiency. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of the present invention is to provide a high-strength ivory white ceramic glaze, a ceramic having the glaze and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0006] The present invention solves the technical problem by adopting the following technical solution:
[0007] The present invention provides a high-strength ivory white ceramic glaze, comprising the following raw materials in parts by weight:
[0008] 15-20 parts of Dehua quartz, 10-15 parts of Dehua kaolin, 8-12 parts of Dehua potassium feldspar, 6-9 parts of balancing agent doped with modified fillers, 4-7 parts of chitosan liquid, and 3-5 parts of calcium stearate;
[0009] The preparation method of the chitosan solution is:
[0010] The wollastonite is first placed in a proton irradiation box for irradiation for 10-15 minutes at an irradiation power of 350-400W, and after the irradiation is completed, an irradiated wollastonite agent is obtained;
[0011] By weight, 3-5 parts of silane coupling agent KH550 and 1-2 parts of sodium dodecylbenzene sulfonate are added to 5-8 parts of chitosan solution with a mass fraction of 2-5%, and then 2-4 parts of irradiated wollastonite are added and stirred thoroughly to obtain chitosan solution.
[0012] Preferably, the high-strength ivory white ceramic glaze comprises the following raw materials in parts by weight:
[0013] 17.5 parts of Dehua quartz, 12.5 parts of Dehua kaolin, 10 parts of Dehua potassium feldspar, 7.5 parts of balancing agent for doped modified fillers, 5.5 parts of chitosan liquid, and 4 parts of calcium stearate.
[0014] Preferably, the preparation method of the balancing agent for doping and modifying fillers is:
[0015] S01: calcining the nano-attapulgite at 215-225°C for 15-20 min, cooling to 60°C at a rate of 2°C / min, and keeping the temperature to obtain the heat-insulated nano-attapulgite;
[0016] The insulated nano-attapulgite is stirred sufficiently in a sufficient amount of a 5% by mass potassium permanganate solution, and then washed with water, filtered, and dried to obtain a pretreated nano-attapulgite;
[0017] S02: Add 5 to 8 parts of pretreated nano-attapulgite into 6 to 10 parts of sodium silicate solution by weight and stir evenly, then add 2 to 3 parts of yttrium nitrate solution, 3 to 5 parts of zirconium oxide and 1 to 2 parts of stearic acid and continue stirring sufficiently to obtain a doped modified filler liquid;
[0018] S03: Preparation of balancing agent:
[0019] The nano-silicon dioxide is stirred evenly in a sufficient amount of a 5% sulfuric acid solution, and then filtered and dried to obtain dry nano-silicon dioxide; 5-8 parts of dry nano-silicon dioxide, 1-2 parts of urea, 3-6 parts of a 6% sodium alginate solution and 2-5 parts of hydroxyapatite are mixed and stirred sufficiently by weight, and then filtered and dried to obtain a balancing agent;
[0020] S04: The doped modified filler liquid and the balancing agent are mixed in a weight ratio of 5:3 and subjected to ball milling. After the ball milling is completed, the mixture is filtered and dried to obtain the balancing agent for the doped modified filler.
[0021] Preferably, the mass fraction of the sodium silicate solution is 2-5%; the mass fraction of the yttrium nitrate solution is 3-6%.
[0022] Preferably, the mixing and ball milling treatment is performed at a ball milling speed of 1500-2000 r / min and the ball milling is performed for 2 hours.
[0023] The present invention also provides a high-strength ivory white ceramic, using the high-strength ivory white ceramic glaze, comprising the following steps:
[0024] Step 1: Preparation of high-strength ivory white ceramic glaze:
[0025] The Dehua quartz, Dehua kaolin, Dehua potassium feldspar, a balancing agent doped with modified fillers, chitosan solution and calcium stearate were mixed and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours to obtain a high-strength ivory white ceramic glaze.
[0026] Step 2: 10-15 parts of albite, 8-12 parts of calcined talc, 5-7 parts of illite, 3-5 parts of silicon carbide, 5-8 parts of a barium nitrate-modified adjusting agent and 8-12 parts of water are mixed and wet-milled at a ball milling speed of 1000 r / min for 2 hours to obtain a blank; the blank is molded at a molding pressure of 75-85 MPa for 30 minutes to obtain a blank;
[0027] Step 3: Apply high-strength ivory white ceramic glaze to the surface of the body, with a glaze amount of 600-650g / m 2 , then sintered at 1250℃ for 2h. After the sintering was completed, it was cooled to 750℃ at a rate of 5~8℃ / min and continued to sinter for 1h to obtain high-strength ivory white ceramics.
[0028] Preferably, the preparation method of the barium nitrate-modified adjusting agent is:
[0029] S11: preheating the boron nitride flake at 60-65°C for 10 min, then heating it to 120-130°C at a rate of 1-3°C / min, keeping the temperature for 20 min, and then air-cooling it to room temperature to obtain preheated boron nitride flake;
[0030] S12: subjecting the preheated boron nitride flakes and the barium nitrate-based modification liquid to an oscillation modification treatment at a weight ratio of 2:5, filtering and drying after the oscillation is completed, to obtain a barium nitrate-modified adjustment agent;
[0031] The preparation method of the modified liquid based on barium nitrate is as follows:
[0032] By weight, 2 to 5 parts of barium nitrate solution and 2 to 4 parts of basalt fiber are added to 5 to 8 parts of lanthanum chloride solution, and then 1 to 3 parts of silane coupling agent KH560 are added and stirred thoroughly to obtain a modified solution based on barium nitrate.
[0033] Preferably, the oscillation power of the oscillation modification treatment is 400-500 W, and the oscillation time is 20-30 min.
[0034] Preferably, the mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the barium nitrate solution is 2-3%.
[0035] The invention also provides a high-strength ivory white ceramic, which is prepared by the preparation method of the high-strength ivory white ceramic.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The high-strength ivory white ceramic glaze of the present invention uses Dehua quartz, Dehua kaolin, and Dehua potassium feldspar as matrix raw materials, and is blended and coordinated by a balancing agent doped with modified fillers, chitosan liquid, and calcium stearate. At the same time, the product is wet-milled by mixing sodium feldspar, calcined talc, illite, silicon carbide, a blending agent based on barium nitrate modification, and water during preparation. Through the blending and coordination between the raw materials, and then the blank molding treatment, and finally the sintering improvement, the compressive strength and fracture toughness of the obtained ceramic product are coordinated with the ivory white and color uniformity of the product. At the same time, the product has a significant product stability effect under acid and alkali corrosion conditions;
[0038] 2. The balancing agent for doped and modified fillers is prepared by calcining nano-attapulgite at 215-225°C for 15-20 minutes, and then cooling to 60°C at a rate of 2°C / min to optimize the interlayer spacing and interlayer spacing activity of the nano-attapulgite, so as to facilitate better coordination with sodium silicate solution, yttrium nitrate solution, zirconium oxide and stearic acid to form a doped and modified filler solution. The interfacial activity of the raw materials is optimized through coordination between the raw materials. The nano-silica is then activated by an acid solution to optimize the activity energy. The urea, a 6% sodium alginate solution and hydroxyapatite are coordinated and coordinated with each other. The hydroxyapatite is carried by nano-silica with a high surface area through coordination between the raw materials, and then the nano-attapulgite is coordinated. The prepared balancing agent for doped and modified fillers can better optimize the ivory whiteness and color uniformity of the product in the system, and improve the acid and alkali corrosion stability of the product.
[0039] 3. Chitosan liquid uses wollastonite after proton irradiation to stimulate the active efficiency, and then cooperates with silane coupling agent KH550, sodium dodecylbenzene sulfonate and chitosan solution with a mass fraction of 2-5%. Through the coordination and matching of the raw materials, wollastonite is used as the needle-shaped structure to strengthen the system structure performance. At the same time, the chitosan solution, silane coupling agent KH550 and sodium dodecylbenzene sulfonate are coordinated to jointly improve the interface of the balancing agent of the doped modified filler in the system, so as to better play its supplementary filling effect, and then the performance effect of the product is further improved;
[0040] 4. The barium nitrate-modified adjusting agent uses flake boron nitride to be preheated at 60-65°C for 10 minutes, and then heated to 120-130°C at a rate of 1-3°C / min and kept warm for 20 minutes. The activity performance of the preheated flake boron nitride is improved. At the same time, the barium nitrate-based modified liquid is blended with barium nitrate solution, basalt fiber, lanthanum chloride solution and silane coupling agent KH560. Through the co-matching and co-assistance of the raw materials, the system structure is reinforced with basalt fiber, and then combined with the preheated flake boron nitride, the system performance coordination and product performance stability are enhanced in the system. DETAILED DESCRIPTION
[0041] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] A high-strength ivory white ceramic glaze of this embodiment includes the following raw materials in parts by weight:
[0043] 15-20 parts of Dehua quartz, 10-15 parts of Dehua kaolin, 8-12 parts of Dehua potassium feldspar, 6-9 parts of balancing agent doped with modified fillers, 4-7 parts of chitosan liquid, and 3-5 parts of calcium stearate;
[0044] The preparation method of the chitosan solution is:
[0045] The wollastonite is first placed in a proton irradiation box for irradiation for 10-15 minutes at an irradiation power of 350-400W, and after the irradiation is completed, an irradiated wollastonite agent is obtained;
[0046] By weight, 3-5 parts of silane coupling agent KH550 and 1-2 parts of sodium dodecylbenzene sulfonate are added to 5-8 parts of chitosan solution with a mass fraction of 2-5%, and then 2-4 parts of irradiated wollastonite are added and stirred thoroughly to obtain chitosan solution.
[0047] The preparation method of the balancing agent for doping and modifying fillers in this embodiment is as follows:
[0048] S01: calcining the nano-attapulgite at 215-225°C for 15-20 min, cooling to 60°C at a rate of 2°C / min, and keeping the temperature to obtain the heat-insulated nano-attapulgite;
[0049] The insulated nano-attapulgite is stirred sufficiently in a sufficient amount of a 5% by mass potassium permanganate solution, and then washed with water, filtered, and dried to obtain a pretreated nano-attapulgite;
[0050] S02: Add 5 to 8 parts of pretreated nano-attapulgite into 6 to 10 parts of sodium silicate solution by weight and stir evenly, then add 2 to 3 parts of yttrium nitrate solution, 3 to 5 parts of zirconium oxide and 1 to 2 parts of stearic acid and continue stirring sufficiently to obtain a doped modified filler liquid;
[0051] S03: Preparation of balancing agent:
[0052] The nano-silicon dioxide is stirred evenly in a sufficient amount of a 5% sulfuric acid solution, and then filtered and dried to obtain dry nano-silicon dioxide; 5-8 parts of dry nano-silicon dioxide, 1-2 parts of urea, 3-6 parts of a 6% sodium alginate solution and 2-5 parts of hydroxyapatite are mixed and stirred sufficiently by weight, and then filtered and dried to obtain a balancing agent;
[0053] S04: The doped modified filler liquid and the balancing agent are mixed in a weight ratio of 5:3 and subjected to ball milling. After the ball milling is completed, the mixture is filtered and dried to obtain the balancing agent for the doped modified filler.
[0054] The mass fraction of the sodium silicate solution in this embodiment is 2-5%; the mass fraction of the yttrium nitrate solution is 3-6%.
[0055] The mixing and ball milling process of this embodiment has a ball milling speed of 1500-2000 r / min and a ball milling time of 2 h.
[0056] A high-strength ivory white ceramic of this embodiment includes the following steps:
[0057] Step 1: Preparation of high-strength ivory white ceramic glaze:
[0058] The Dehua quartz, Dehua kaolin, Dehua potassium feldspar, a balancing agent doped with modified fillers, chitosan solution and calcium stearate were mixed and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours to obtain a high-strength ivory white ceramic glaze.
[0059] Step 2: 10-15 parts of albite, 8-12 parts of calcined talc, 5-7 parts of illite, 3-5 parts of silicon carbide, 5-8 parts of a barium nitrate-modified adjusting agent and 8-12 parts of water are mixed and wet-milled at a ball milling speed of 1000 r / min for 2 hours to obtain a blank; the blank is molded at a molding pressure of 75-85 MPa for 30 minutes to obtain a blank;
[0060] Step 3: Apply high-strength ivory white ceramic glaze to the surface of the body, with a glaze amount of 600-650g / m 2 , then sintered at 1250℃ for 2h. After the sintering was completed, it was cooled to 750℃ at a rate of 5~8℃ / min and continued to sinter for 1h to obtain high-strength ivory white ceramics.
[0061] The preparation method of the barium nitrate modified adjusting agent in this embodiment is as follows:
[0062] S11: preheating the boron nitride flake at 60-65°C for 10 min, then heating it to 120-130°C at a rate of 1-3°C / min, keeping the temperature for 20 min, and then air-cooling it to room temperature to obtain preheated boron nitride flake;
[0063] S12: subjecting the preheated boron nitride flakes and the barium nitrate-based modification liquid to an oscillation modification treatment at a weight ratio of 2:5, filtering and drying after the oscillation is completed, to obtain a barium nitrate-modified adjustment agent;
[0064] The preparation method of the modified liquid based on barium nitrate is as follows:
[0065] By weight, 2 to 5 parts of barium nitrate solution and 2 to 4 parts of basalt fiber are added to 5 to 8 parts of lanthanum chloride solution, and then 1 to 3 parts of silane coupling agent KH560 are added and stirred thoroughly to obtain a modified solution based on barium nitrate.
[0066] The oscillation power of the oscillation modification treatment in this embodiment is 400-500 W, and the oscillation time is 20-30 min.
[0067] The mass fraction of the lanthanum chloride solution in this embodiment is 3-5%; the mass fraction of the barium nitrate solution is 2-3%.
[0068] The high-strength ivory white ceramic of this embodiment is prepared by the preparation method of the high-strength ivory white ceramic.
[0069] Example 1: A high-strength ivory white ceramic glaze, comprising the following raw materials in parts by weight:
[0070] 15 parts of Dehua quartz, 10 parts of Dehua kaolin, 8 parts of Dehua potassium feldspar, 6 parts of balancing agent doped with modified fillers, 4 parts of chitosan liquid, and 3 parts of calcium stearate;
[0071] The preparation method of the chitosan solution is:
[0072] The wollastonite is first placed in a proton irradiation box for irradiation for 10 minutes at an irradiation power of 350W, and after the irradiation is completed, an irradiated wollastonite agent is obtained;
[0073] According to weight, 3 parts of silane coupling agent KH550 and 1 part of sodium dodecylbenzene sulfonate were added to 5 parts of 2% chitosan solution, and then 2 parts of irradiated wollastonite were added and stirred thoroughly to obtain chitosan solution.
[0074] The preparation method of the balancing agent for doping and modifying fillers in this embodiment is as follows:
[0075] S01: calcining the nano-attapulgite at 215° C. for 15 min, cooling to 60° C. at a rate of 2° C. / min, and keeping the temperature to obtain the heat-insulated nano-attapulgite;
[0076] The insulated nano-attapulgite is stirred sufficiently in a sufficient amount of a 5% by mass potassium permanganate solution, and then washed with water, filtered, and dried to obtain a pretreated nano-attapulgite;
[0077] S02: Add 5 parts of pretreated nano-attapulgite into 6 parts of sodium silicate solution by weight and stir evenly, then add 2 parts of yttrium nitrate solution, 3 parts of zirconium oxide and 1 part of stearic acid and continue stirring sufficiently to obtain a doped modified filler solution;
[0078] S03: Preparation of balancing agent:
[0079] The nano-silicon dioxide is stirred evenly in a sufficient amount of a sulfuric acid solution with a mass fraction of 5%, and then filtered and dried to obtain dry nano-silicon dioxide; 5 parts of dry nano-silicon dioxide, 1 part of urea, 3 parts of a sodium alginate solution with a mass fraction of 6% and 2 parts of hydroxyapatite are mixed and stirred sufficiently, and then filtered and dried to obtain a balancing agent;
[0080] S04: The doped modified filler liquid and the balancing agent are mixed in a weight ratio of 5:3 and subjected to ball milling. After the ball milling is completed, the mixture is filtered and dried to obtain the balancing agent for the doped modified filler.
[0081] The mass fraction of the sodium silicate solution in this embodiment is 2%; the mass fraction of the yttrium nitrate solution is 3%.
[0082] The mixing and ball milling process in this embodiment was carried out at a ball milling speed of 1500 r / min and the ball milling was carried out for 2 h.
[0083] A high-strength ivory white ceramic of this embodiment is characterized by comprising the following steps:
[0084] Step 1: Preparation of high-strength ivory white ceramic glaze:
[0085] The Dehua quartz, Dehua kaolin, Dehua potassium feldspar, a balancing agent doped with modified fillers, chitosan solution and calcium stearate were mixed and ball-milled at a speed of 1000 r / min for 2 h to obtain a high-strength ivory white ceramic glaze.
[0086] Step 2: 10 parts of albite, 8 parts of calcined talc, 5 parts of illite, 3 parts of silicon carbide, 5 parts of a barium nitrate-modified conditioning agent and 8 parts of water are mixed and wet-milled at a ball milling speed of 1000 r / min for 2 hours to obtain a blank; the blank is molded at a molding pressure of 75 MPa for 30 minutes to obtain a blank;
[0087] Step 3: Apply high-strength ivory white ceramic glaze to the surface of the body, with a glaze amount of 600g / m 2 , then sintered at 1250℃ for 2h. After the sintering was completed, it was cooled to 750℃ at a rate of 5℃ / min and continued to sinter for 1h to obtain high-strength ivory white ceramics.
[0088] The preparation method of the barium nitrate modified adjusting agent in this embodiment is as follows:
[0089] S11: preheating the boron nitride flake at 60°C for 10 minutes, then heating it to 120°C at a rate of 1°C / min, keeping it at that temperature for 20 minutes, and then air-cooling it to room temperature to obtain preheated boron nitride flake;
[0090] S12: subjecting the preheated boron nitride flakes and the barium nitrate-based modification liquid to an oscillation modification treatment at a weight ratio of 2:5, filtering and drying after the oscillation is completed, to obtain a barium nitrate-modified adjustment agent;
[0091] The preparation method of the modified liquid based on barium nitrate is as follows:
[0092] According to weight, 2 parts of barium nitrate solution and 2 parts of basalt fiber were added to 5 parts of lanthanum chloride solution, and then 1 part of silane coupling agent KH560 was added and stirred thoroughly to obtain a modified solution based on barium nitrate.
[0093] The oscillation power of the oscillation modification treatment in this embodiment is 400 W, and the oscillation time is 20 min.
[0094] The mass fraction of the lanthanum chloride solution in this embodiment is 3%; the mass fraction of the barium nitrate solution is 2%.
[0095] The high-strength ivory white ceramic of this embodiment is prepared by the preparation method of the high-strength ivory white ceramic.
[0096] Example 2: A high-strength ivory white ceramic glaze, comprising the following raw materials in parts by weight:
[0097] 20 parts of Dehua quartz, 15 parts of Dehua kaolin, 12 parts of Dehua potassium feldspar, 9 parts of balancing agent doped with modified fillers, 7 parts of chitosan liquid, and 5 parts of calcium stearate;
[0098] The preparation method of the chitosan solution is:
[0099] The wollastonite is first placed in a proton irradiation box for irradiation for 15 minutes at an irradiation power of 400 W. After the irradiation is completed, an irradiated wollastonite agent is obtained;
[0100] According to weight, 5 parts of silane coupling agent KH550 and 2 parts of sodium dodecylbenzene sulfonate were added to 8 parts of 5% chitosan solution, and then 4 parts of irradiated wollastonite were added and stirred thoroughly to obtain chitosan solution.
[0101] The preparation method of the balancing agent for doping and modifying fillers in this embodiment is as follows:
[0102] S01: calcining the nano-attapulgite at 225° C. for 20 min, cooling to 60° C. at a rate of 2° C. / min, and keeping the temperature to obtain the heat-insulated nano-attapulgite;
[0103] The insulated nano-attapulgite is stirred sufficiently in a sufficient amount of a 5% by mass potassium permanganate solution, and then washed with water, filtered, and dried to obtain a pretreated nano-attapulgite;
[0104] S02: Add 8 parts of pretreated nano-attapulgite into 10 parts of sodium silicate solution by weight and stir evenly, then add 3 parts of yttrium nitrate solution, 5 parts of zirconium oxide and 2 parts of stearic acid and continue stirring sufficiently to obtain a doped modified filler solution;
[0105] S03: Preparation of balancing agent:
[0106] The nano-silicon dioxide is stirred evenly in a sufficient amount of a sulfuric acid solution with a mass fraction of 5%, and then filtered and dried to obtain dry nano-silicon dioxide; 8 parts of dry nano-silicon dioxide, 2 parts of urea, 6 parts of a sodium alginate solution with a mass fraction of 6% and 5 parts of hydroxyapatite are mixed and stirred sufficiently, and then filtered and dried to obtain a balancing agent;
[0107] S04: The doped modified filler liquid and the balancing agent are mixed in a weight ratio of 5:3 and subjected to ball milling. After the ball milling is completed, the mixture is filtered and dried to obtain the balancing agent for the doped modified filler.
[0108] The mass fraction of the sodium silicate solution in this embodiment is 5%; the mass fraction of the yttrium nitrate solution is 6%.
[0109] The mixing and ball milling process in this embodiment was carried out at a ball milling speed of 2000 r / min and the ball milling was carried out for 2 h.
[0110] A high-strength ivory white ceramic of this embodiment is characterized by comprising the following steps:
[0111] Step 1: Preparation of high-strength ivory white ceramic glaze:
[0112] The Dehua quartz, Dehua kaolin, Dehua potassium feldspar, a balancing agent doped with modified fillers, chitosan solution and calcium stearate were mixed and ball-milled at a speed of 1500 r / min for 2 h to obtain a high-strength ivory white ceramic glaze.
[0113] Step 2: 15 parts of albite, 12 parts of calcined talc, 7 parts of illite, 5 parts of silicon carbide, 8 parts of a barium nitrate-modified feed agent and 12 parts of water are mixed and wet-milled at a ball milling speed of 1000 r / min for 2 hours to obtain a blank; the blank is molded at a molding pressure of 85 MPa for 30 minutes to obtain a blank;
[0114] Step 3: Apply high-strength ivory white ceramic glaze to the surface of the body, with a glaze amount of 650g / m 2, then sintered at 1250℃ for 2h. After the sintering was completed, it was cooled to 750℃ at a rate of 8℃ / min and continued to sinter for 1h to obtain high-strength ivory white ceramics.
[0115] The preparation method of the barium nitrate modified adjusting agent in this embodiment is as follows:
[0116] S11: preheating the boron nitride flake at 65°C for 10 minutes, then heating it to 130°C at a rate of 3°C / min, keeping it at that temperature for 20 minutes, and then air-cooling it to room temperature to obtain preheated boron nitride flake;
[0117] S12: subjecting the preheated boron nitride flakes and the barium nitrate-based modification liquid to an oscillation modification treatment at a weight ratio of 2:5, filtering and drying after the oscillation is completed, to obtain a barium nitrate-modified adjustment agent;
[0118] The preparation method of the modified liquid based on barium nitrate is as follows:
[0119] According to weight, 5 parts of barium nitrate solution and 4 parts of basalt fiber were added to 8 parts of lanthanum chloride solution, and then 3 parts of silane coupling agent KH560 were added and stirred thoroughly to obtain a modified solution based on barium nitrate.
[0120] The oscillation power of the oscillation modification treatment in this embodiment is 500 W, and the oscillation time is 30 min.
[0121] The mass fraction of the lanthanum chloride solution in this embodiment is 5%; the mass fraction of the barium nitrate solution is 3%.
[0122] The high-strength ivory white ceramic of this embodiment is prepared by the preparation method of the high-strength ivory white ceramic.
[0123] Example 3: A high-strength ivory white ceramic glaze, comprising the following raw materials in parts by weight:
[0124] 17.5 parts of Dehua quartz, 12.5 parts of Dehua kaolin, 10 parts of Dehua potassium feldspar, 7.5 parts of balancing agent for doping and modifying fillers, 5.5 parts of chitosan liquid, and 4 parts of calcium stearate;
[0125] The preparation method of the chitosan solution is:
[0126] The wollastonite was first placed in a proton irradiation box for irradiation for 12.5 minutes at an irradiation power of 375 W. After the irradiation was completed, an irradiated wollastonite agent was obtained.
[0127] According to weight, 4 parts of silane coupling agent KH550 and 1.5 parts of sodium dodecylbenzene sulfonate were added to 6.5 parts of chitosan solution with a mass fraction of 3.5%, and then 3 parts of irradiated wollastonite were added and stirred thoroughly to obtain chitosan solution.
[0128] The preparation method of the balancing agent for doping and modifying fillers in this embodiment is as follows:
[0129] S01: calcining the nano-attapulgite at 220° C. for 17.5 min, cooling to 60° C. at a rate of 2° C. / min, and keeping the temperature to obtain the heat-insulated nano-attapulgite;
[0130] The insulated nano-attapulgite is stirred sufficiently in a sufficient amount of a 5% by mass potassium permanganate solution, and then washed with water, filtered, and dried to obtain a pretreated nano-attapulgite;
[0131] S02: Add 6.5 parts of pretreated nano-attapulgite into 8 parts of sodium silicate solution by weight and stir evenly, then add 2.5 parts of yttrium nitrate solution, 4 parts of zirconium oxide and 1.5 parts of stearic acid and continue stirring sufficiently to obtain a doped modified filler liquid;
[0132] S03: Preparation of balancing agent:
[0133] The nano-silicon dioxide is stirred evenly in a sufficient amount of a sulfuric acid solution with a mass fraction of 5%, and then filtered and dried to obtain dry nano-silicon dioxide; 6.5 parts of dry nano-silicon dioxide, 1.5 parts of urea, 4.5 parts of a sodium alginate solution with a mass fraction of 6% and 3.5 parts of hydroxyapatite are mixed and stirred sufficiently, and then filtered and dried to obtain a balancing agent;
[0134] S04: The doped modified filler liquid and the balancing agent are mixed in a weight ratio of 5:3 and subjected to ball milling. After the ball milling is completed, the mixture is filtered and dried to obtain the balancing agent for the doped modified filler.
[0135] The mass fraction of the sodium silicate solution in this embodiment is 3.5%; the mass fraction of the yttrium nitrate solution is 4.5%.
[0136] The mixing ball milling process in this embodiment was carried out at a ball milling speed of 1750 r / min and the ball milling was carried out for 2 h.
[0137] A high-strength ivory white ceramic of this embodiment is characterized by comprising the following steps:
[0138] Step 1: Preparation of high-strength ivory white ceramic glaze:
[0139] Dehua quartz, Dehua kaolin, Dehua potassium feldspar, a balancing agent doped with modified fillers, chitosan solution and calcium stearate were mixed and ball-milled at a ball-milling speed of 1250 r / min for 2 h to obtain a high-strength ivory white ceramic glaze.
[0140] Step 2: 12.5 parts of albite, 10 parts of calcined talc, 6 parts of illite, 4 parts of silicon carbide, 6.5 parts of a barium nitrate-modified conditioning agent and 10 parts of water are mixed and wet-milled at a ball milling speed of 1000 r / min for 2 hours to obtain a blank; the blank is molded at a molding pressure of 80 MPa for 30 minutes to obtain a blank;
[0141] Step 3: Apply high-strength ivory white ceramic glaze to the surface of the body, with a glaze amount of 625g / m 2 , then sintered at 1250℃ for 2h. After the sintering was completed, it was cooled to 750℃ at a rate of 6.5℃ / min and continued to sinter for 1h to obtain high-strength ivory white ceramics.
[0142] The preparation method of the barium nitrate modified adjusting agent in this embodiment is as follows:
[0143] S11: preheating the boron nitride flake at 62.5°C for 10 min, then heating it to 125°C at a rate of 2°C / min, keeping it at that temperature for 20 min, and then air-cooling it to room temperature to obtain preheated boron nitride flake;
[0144] S12: subjecting the preheated boron nitride flakes and the barium nitrate-based modification liquid to an oscillation modification treatment at a weight ratio of 2:5, filtering and drying after the oscillation is completed, to obtain a barium nitrate-modified adjustment agent;
[0145] The preparation method of the modified liquid based on barium nitrate is as follows:
[0146] By weight, 3.5 parts of barium nitrate solution and 3 parts of basalt fiber were added to 6.5 parts of lanthanum chloride solution, and then 2 parts of silane coupling agent KH560 were added and stirred thoroughly to obtain a modified solution based on barium nitrate.
[0147] The oscillation power of the oscillation modification treatment in this embodiment is 450 W, and the oscillation time is 25 min.
[0148] The mass fraction of the lanthanum chloride solution in this embodiment is 4%; the mass fraction of the barium nitrate solution is 2.5%.
[0149] The high-strength ivory white ceramic of this embodiment is prepared by the preparation method of the high-strength ivory white ceramic.
[0150] Comparative Example 1:
[0151] The difference from Example 3 is that no balancing agent for doping and modifying the filler is added.
[0152] Comparative Example 2:
[0153] The difference from Example 3 is that no doped modified filler liquid is added in the preparation of the balancing agent for the doped modified filler.
[0154] Comparative Example 3:
[0155] The difference from Example 3 is that no pretreated nano-attapulgite is added in the preparation of the doped modified filler liquid.
[0156] Comparative Example 4:
[0157] The difference from Example 3 is that no yttrium nitrate solution and zirconium oxide are added in the preparation of the doped modified filler liquid.
[0158] Comparative Example 5:
[0159] The difference from Example 3 is that no balancing agent is added in the preparation of the balancing agent for doping and modifying the filler.
[0160] Comparative Example 6:
[0161] The difference from Example 3 is that no dry nano-silicon dioxide or urea is added to the balancing agent.
[0162] Comparative Example 7:
[0163] The difference from Example 3 is that hydroxyapatite is not added to the balancing agent, and the sodium alginate solution is replaced by water.
[0164] Comparative Example 8:
[0165] The difference from Example 3 is that no chitosan solution was added.
[0166] Comparative Example 9:
[0167] The difference from Example 3 is that no irradiated wollastonite agent is added to the chitosan solution.
[0168] Comparative Example 10:
[0169] The difference from Example 3 is that no silane coupling agent KH550 or sodium dodecylbenzene sulfonate is added to the chitosan solution.
[0170] Comparative Example 11:
[0171] The difference from Example 3 is that no barium nitrate-modified conditioning agent is added.
[0172] Comparative Example 12:
[0173] The difference from Example 3 is that no preheated flake boron nitride is added in the preparation of the barium nitrate modified feed agent.
[0174] Comparative Example 13:
[0175] The difference from Example 3 is that no barium nitrate-based modifying liquid is added in the preparation of the barium nitrate-modified adjusting agent.
[0176] The ceramic products of Examples 1 to 3 and Comparative Examples 1 to 13 were subjected to conventional performance tests. The products were placed in a 2% hydrochloric acid mist condition for 12 hours and then placed in a 5% sodium hydroxide solution alkaline mist condition for 12 hours to test the acid and alkali stability of the products. The test results are shown in Table 1.
[0177] Table 1 Performance test results of ceramic products of Examples 1 to 3 and Comparative Examples 1 to 13:
[0178]
[0179] It can be seen from Comparative Examples 1-13 and Examples 1-3 that the product of Example 3 has excellent compressive strength and fracture toughness, and the product has ivory white color and uniform color, and the acid and alkali resistance stability of the product is remarkable;
[0180] The product does not contain any of the following: a balancing agent for doping modified fillers, chitosan solution, or a conditioning agent based on barium nitrate modification. The product's performance coordination and stability have a significant deterioration trend. The product performance is most significant when the three are coordinated and work together.
[0181] In the preparation of the balancing agent for the doped and modified filler, no doped and modified filler liquid was added, no pretreated nano-attapulgite was added, no yttrium nitrate solution and zirconium oxide were added, no balancing agent was added, no dried nano-silicon dioxide and urea were added to the balancing agent, and no hydroxyapatite was added to the balancing agent. The sodium alginate solution was replaced by water. The performance of the product showed a trend of varying degrees of deterioration. The balancing agent for the doped and modified filler prepared by the balancing agent obtained by the specific method of the present invention and the specific doped and modified filler liquid had the most obvious product performance effect. The replacement by other methods was not as obvious as the effect of the present invention.
[0182] The performance of the product also showed a trend of deterioration when no irradiated wollastonite agent, silane coupling agent KH550 and sodium dodecylbenzene sulfonate were added to the chitosan solution;
[0183] In the preparation of the barium nitrate-modified adjusting agent, no preheated flake boron nitride was added, and in the preparation of the barium nitrate-modified adjusting agent, no barium nitrate-based modifying liquid was added. The performance of the products tended to deteriorate. The barium nitrate-modified adjusting agent obtained by the specific method of the present invention had the most obvious product performance effect.
[0184] At the same time, the inventors of the present invention also found that without adding the barium nitrate-based modifying liquid, the stability of the product under acid-base corrosion conditions deteriorated significantly. Based on this, the present invention further explored the effect of the preparation of the barium nitrate-based modifying liquid on the product performance.
[0185] Experimental Example 1:
[0186] The only difference from Example 3 is that no barium nitrate solution is added to the barium nitrate-based modifying solution.
[0187] Experimental Example 2:
[0188] The only difference from Example 3 is that no basalt fiber is added to the barium nitrate-based modifying solution.
[0189] Experimental Example 3:
[0190] The only difference from Example 3 is that no lanthanum chloride solution is added to the barium nitrate-based modifying solution.
[0191] Experimental Example 4:
[0192] The only difference from Example 3 is that the silane coupling agent KH560 is not added to the barium nitrate-based modifying liquid.
[0193] Experimental Example 5:
[0194] The only difference from Example 3 is that the mass fraction of the lanthanum chloride solution is 2%; the mass fraction of the barium nitrate solution is 4%.
[0195] The ceramic products of Experimental Examples 1 to 5 were subjected to conventional performance tests. At the same time, the products were placed in 2% hydrochloric acid mist conditions for 12 hours and then placed in 5% sodium hydroxide solution alkaline mist conditions for 12 hours to test the acid and alkali stability of the products. The test results are shown in Table 2.
[0196] Table 2 Performance test results of ceramic products in Experimental Examples 1 to 5:
[0197]
[0198] It can be seen from Experimental Examples 1-5 that basalt fiber is not added to the barium nitrate-based modifying liquid, and the performance changes of the product are most obvious in the preparation factors of the barium nitrate-based modifying liquid, followed by the fact that no barium nitrate solution is added to the barium nitrate-based modifying liquid, and at the same time, no lanthanum chloride solution is added to the barium nitrate-based modifying liquid, no silane coupling agent KH560 is added to the barium nitrate-based modifying liquid, and the mass fraction of lanthanum chloride solution is 2%; the mass fraction of the barium nitrate solution is 4%, and the performance of the product has a tendency to deteriorate. The preparation process of the barium nitrate-based modifying liquid is unique. Only the barium nitrate-based modifying liquid obtained by the specific method and raw materials of the present invention has the most significant performance effect of the product. The use of other methods instead is not as significant as the effect of the present invention. At the same time, the mass fraction of the raw materials of the present invention is also unique. If the mass fraction is not within the range of the present invention, the performance of the product also tends to deteriorate.
[0199] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0200] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A high-strength ivory white ceramic glaze, characterized in that: It includes the following raw materials in parts by weight: 15-20 parts of Dehua quartz, 10-15 parts of Dehua kaolin, 8-12 parts of Dehua potassium feldspar, 6-9 parts of balancing agent doped with modified fillers, 4-7 parts of chitosan liquid, and 3-5 parts of calcium stearate; The preparation method of the balancing agent for doping and modifying fillers is as follows: S01: calcining the nano-attapulgite at 215-225°C for 15-20 min, cooling to 60°C at a rate of 2°C / min, and keeping the temperature to obtain the heat-insulated nano-attapulgite; The heat-insulated nano-attapulgite is stirred sufficiently in a sufficient amount of a 5% by mass potassium permanganate solution, and then washed, filtered, and dried to obtain a pretreated nano-attapulgite; S02: Add 5 to 8 parts of pretreated nano-attapulgite into 6 to 10 parts of sodium silicate solution by weight and stir evenly, then add 2 to 3 parts of yttrium nitrate solution, 3 to 5 parts of zirconium oxide and 1 to 2 parts of stearic acid and continue stirring sufficiently to obtain a doped modified filler liquid; S03: Preparation of balancing agent: The nano-silicon dioxide is stirred evenly in a sufficient amount of a 5% sulfuric acid solution, and then filtered and dried to obtain dry nano-silicon dioxide; 5-8 parts of dry nano-silicon dioxide, 1-2 parts of urea, 3-6 parts of a 6% sodium alginate solution and 2-5 parts of hydroxyapatite are mixed and stirred sufficiently by weight, and then filtered and dried to obtain a balancing agent; S04: mixing the doped modified filler liquid and the balancing agent in a weight ratio of 5:3 and subjecting the mixture to ball milling. After the ball milling is completed, the mixture is filtered and dried to obtain the balancing agent for the doped modified filler; The preparation method of the chitosan solution is: The wollastonite is first placed in a proton irradiation box for irradiation for 10-15 minutes at an irradiation power of 350-400W, and after the irradiation is completed, an irradiated wollastonite agent is obtained; By weight, 3-5 parts of silane coupling agent KH550 and 1-2 parts of sodium dodecylbenzene sulfonate are added to 5-8 parts of chitosan solution with a mass fraction of 2-5%, and then 2-4 parts of irradiated wollastonite are added and stirred thoroughly to obtain chitosan solution.
2. The high-strength ivory white ceramic glaze according to claim 1, characterized in that: The high-strength ivory white ceramic glaze comprises the following raw materials in parts by weight: 17.5 parts of Dehua quartz, 12.5 parts of Dehua kaolin, 10 parts of Dehua potassium feldspar, 7.5 parts of balancing agent for doped modified fillers, 5.5 parts of chitosan liquid, and 4 parts of calcium stearate.
3. The high-strength ivory white ceramic glaze according to claim 2, characterized in that: The mass fraction of the sodium silicate solution is 2-5%.
4. The high-strength ivory white ceramic glaze according to claim 2, characterized in that: The mass fraction of the yttrium nitrate solution is 3-6%.
5. The high-strength ivory white ceramic glaze according to claim 2, characterized in that: The mixing and ball milling process is performed at a ball milling speed of 1500-2000 r / min and the ball milling is performed for 2 hours.
6. A method for preparing high-strength ivory white ceramics, using the high-strength ivory white ceramic glaze according to claim 1, characterized in that: The following steps are involved: Step 1: Preparation of high-strength ivory white ceramic glaze: The Dehua quartz, Dehua kaolin, Dehua potassium feldspar, a balancing agent doped with modified fillers, chitosan solution and calcium stearate were mixed and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours to obtain a high-strength ivory white ceramic glaze. Step 2: 10-15 parts of albite, 8-12 parts of calcined talc, 5-7 parts of illite, 3-5 parts of silicon carbide, 5-8 parts of a barium nitrate-modified adjusting agent and 8-12 parts of water are mixed and wet-milled at a ball milling speed of 1000 r / min for 2 hours to obtain a blank; the blank is molded at a molding pressure of 75-85 MPa for 30 minutes to obtain a blank; The preparation method of the barium nitrate-modified adjusting agent is as follows: S11: preheating the boron nitride flake at 60-65°C for 10 min, then heating it to 120-130°C at a rate of 1-3°C / min, keeping the temperature for 20 min, and then air-cooling it to room temperature to obtain preheated boron nitride flake; S12: subjecting the preheated boron nitride flakes and the barium nitrate-based modification liquid to an oscillation modification treatment at a weight ratio of 2:5, filtering and drying after the oscillation is completed, to obtain a barium nitrate-modified adjustment agent; The preparation method of the modified liquid based on barium nitrate is as follows: By weight, 2 to 5 parts of barium nitrate solution and 2 to 4 parts of basalt fiber are added to 5 to 8 parts of lanthanum chloride solution, and then 1 to 3 parts of silane coupling agent KH560 are added and stirred sufficiently to obtain a modified solution based on barium nitrate; Step 3: Apply high-strength ivory white ceramic glaze to the surface of the body, with a glaze amount of 600-650g / m 2 , then sintered at 1250℃ for 2h. After the sintering was completed, it was cooled to 750℃ at a rate of 5~8℃ / min and continued to sinter for 1h to obtain high-strength ivory white ceramics.
7. The method for preparing high-strength ivory white ceramics according to claim 6, characterized in that: The oscillation power of the oscillation modification treatment is 400-500W, and the oscillation time is 20-30min.
8. The method for preparing high-strength ivory white ceramics according to claim 6, characterized in that: The mass fraction of the lanthanum chloride solution is 3-5%; the mass fraction of the barium nitrate solution is 2-3%.
9. A high-strength ivory white ceramic prepared by the preparation method of the high-strength ivory white ceramic according to claim 6.
Citation Information
Patent Citations
High-strength whitening glaze slurry for ceramic and preparation method of high-strength whitening glaze slurry
CN106045322A
High-gloss, high-transparency and high-whiteness jade porcelain thin-body glaze and preparation method thereof
CN117700106A